Ibn Arabi’s Epistemological Views In The Context of Sufism and Islamic Philosophy - kizi, Yarashova (Buletin Antropologi Indonesia, 2025)
In this article, issues related to the social, spiritual, and moral essence of humans are discussed within the framework of Eastern philosophy’s ontological, epistemological, axiological, and philosophical-sufistical principles. The development of gnosis, its place in Eastern philosophical thought, the classification of sufistical knowledge, and its importance in filling the gaps in human spirituality, ethics, and morality are analyzed. The theoretical and practical aspects of Sufism based on Ibn Arabi’s sufistical teachings and Sufi science are revealed, along with the concepts of Sharia, Tariqa, and Haqiqa. Furthermore, the methods used by sufis to address religious-philosophical problems, their scientific approaches, and the relationship between the science of jurisprudence and Sufism are analyzed.